Extreme Ventilation of the North Pacific Central Mode Water by El Niño During Positive Phase of the Pacific Decadal Oscillation - Jing Liu; Lixiao Xu; Xiao‐Tong Zheng; Keyao Wang; Junliang Li (Geophysical Research Letters)
Abstract This study investigates the interannual variability of the North Pacific Central Mode Water (CMW) under the phase relationship of the El Niño–Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO), based on multiple observational data sets. Peaks and troughs of the CMW variability are primarily observed when ENSO and PDO are in phase, but only moderate variation when ENSO and PDO are out of phase. In El Niño spring during positive PDO, extreme CMW ventilation takes place in the central North Pacific (180°–155°W, 30°–40°N), where no local ventilation occurs for other cases. Such extreme CMW ventilation induces stronger temperature anomalies, which persist longer and penetrate deeper. Our results suggest that CMW, representing a long‐term ocean memory, may play a more significant role in tropical‐extratropical interactions than ever expected.